Analisis Pengelolaan Koleksi Grey Literatur di Perpustakaan - Kiki, Riski Diana; Mulyadi, Mulyadi (Jurnal El-Pustaka, 2023)
The  purpose  of  this  study  was  to  find  out  how  to  manage  the  gray  literature  collection,  both  theses,  theses  and  dissertations  at  the  UIN  Raden  Fatah  Palembang  Library.  The  method  used  in  this  article  is  a  qualitative  method  with  a  case  study  approach,  with  the  technique  of  collecting  observations  and  literature  sources.  The  results  of  this  article  show  the  management  of  the  gray  literature  collection  (thesis,  thesis  and  dissertation)  at  the  UIN  Raden  Fatah  Palembang  Library.  Where  in  the  thesis  library,  theses  and  accompanied  by  alumni  students  or  students  who  have  just  distributed  theses,  theses  and  dissertations  must  be  managed  first  so  that  information  retrieval  for  students  who  need  references  can  be  easily  found.  And  the  management  of  the  gray  literature  collection  has  been  carried  out  with  the  available  resources,  and  the  management  system  is  structured  from  tasting,  recording,  class,  inputting,  labeling  and  giving  colors  according  to  the  presentation  and  placement  of  theses,  theses  and  dissertations  according  to  the  shelves  of  each  study  program.  However,  the  management  still  needs  improvement  in  several  aspects,  such  as  facilities  such  as  lacking  library  shelves,  networks  and  chips  to detect if  the  thesis  is  taken  or  stolen.